LOOKING FOR THE CAUSES OF A CONVERGENCE: THE CONTRIBUTION OF SOCIAL ANALYSIS ON THE STUDY OF CONTEMPORARY CONSTITUTIONAL LAW - DOI: https://doi.org/10.5216/rfd.v%vi%i.43183 - Paffarini, Jacopo; Caletti, Leandro (Revista da Faculdade de Direito da UFG, 2017)
Abstract: Recent comparative law studies have remarked the role of “metalegal” formants for a complete description of legal language. It is necessary to recognize the dialectic character of a social product – as law – which explain the matters related with a legal command effectiveness. Is the subject of legal studies the construction of a method of social analysis? Or any study must take into consideration any particular social experience without possibility to build a general method? In the first case we affirm that in similar social context the normative rules assume a certain degree of similarity. In the second, we deny any logic of the legal experience: thus, every legal system is “singular”. In order to exit from this contrast, we should look at what is moving inside the social organization and realizing the law “as social practice”. Resumo: Recentes estudos da área de comparação jurídica têm destacado o papel do formato “metalegal” na completa descrição da linguagem normativa. É preciso reconhecer a matriz dialética de um produto social - como o direito - para explicar as problemáticas inerentes à efetividade do comando legal. Seria correto afirmar que o objeto dos estudos jurídicos é a criação de uma metodologia de análise social? Ou, ao contrário, se deveria considerar cada experiência jurídica sem a possibilidade de construir uma metodologia geral? Na primeira hipótese, se afirma que, em contextos similares, as normas apresentam um certo grau de similaridade. Na segunda, é denegada qualquer logica à experiência jurídica: cada sistema é “singular”. Ao efeito de resolver a contradição, se deve olhar para o que se move no interior da organização social, pensando o direito “como pratica social”.